2023
DOI: 10.2169/internalmedicine.0005-22
|View full text |Cite
|
Sign up to set email alerts
|

Nerve Ultrasonography for the Diagnosis and Evaluation of Neuralgic Amyotrophy

Abstract: Neuralgic amyotrophy (NA) is a peripheral nervous system disorder involving multifocal distribution. Although nerve ultrasonography has shown potential for detecting NA lesions, no established detection method exists for distal forearm NA. A 59-year-old man presented with weakness of the muscles innervated by the left posterior interosseous nerve (PIN), median nerve (MN), anterior interosseous nerve (AIN), and ulnar nerve (UN), following severe left shoulder pain. This case suggests that nerve ultrasonography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(26 citation statements)
references
References 8 publications
1
24
1
Order By: Relevance
“…The study is appealing but raises concerns that should be discussed. We disagree with the diagnosis "distal form of neuralgic amyotrophy" [1] . The patient had not only distal forearm pain but also recurrent left shoulder pain, why the clinical presentation suggests proximal and distal neuralgic amyotrophy, also known as Parsonage Turner syndrome (PTS).…”
Section: Introductioncontrasting
confidence: 59%
See 4 more Smart Citations
“…The study is appealing but raises concerns that should be discussed. We disagree with the diagnosis "distal form of neuralgic amyotrophy" [1] . The patient had not only distal forearm pain but also recurrent left shoulder pain, why the clinical presentation suggests proximal and distal neuralgic amyotrophy, also known as Parsonage Turner syndrome (PTS).…”
Section: Introductioncontrasting
confidence: 59%
“…Incomplete recovery could be achieved after one year of follow-up [1] . It was concluded that nerve ultrasound can support the diagnosis of distal neuralgic amyotrophy [1] . The study is appealing but raises concerns that should be discussed.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations